2020
DOI: 10.1016/j.trc.2020.102611
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CAV clustering strategies on mixed traffic flow characteristics: An analysis of vehicle trajectory data

Abstract: Being one of the most promising applications enabled by connected and automated vehicles (CAV) technology, Cooperative Adaptive Cruise Control (CACC) is expected to be deployed in the near term on public roads. Thus far, the majority of the CACC studies have been focusing on the overall network performance with limited insights on the potential impacts of CAVs on human-driven vehicles (HVs). This paper aims to quantify such impacts by studying the high-resolution vehicle trajectory data that are obtained from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…ey observed substantial safety benefits in terms of reduction in traffic conflicts: 12-47% at 25% MPR to 90-94 % at 100% MPR. In [41], TTC was also used to assess the safety conditions for HVs when CAV local clustering strategy was employed. Ali et al found that drivers with advanced traffic information enabled by connectivity tend to wait longer and maintained a larger space on mandatory lane change (the communication delay for lane merging assistance was unnoticeable when it was less than 1.5 s).…”
Section: Cavs and Managed Lanes Managed Lanes Have Been Inmentioning
confidence: 99%
See 1 more Smart Citation
“…ey observed substantial safety benefits in terms of reduction in traffic conflicts: 12-47% at 25% MPR to 90-94 % at 100% MPR. In [41], TTC was also used to assess the safety conditions for HVs when CAV local clustering strategy was employed. Ali et al found that drivers with advanced traffic information enabled by connectivity tend to wait longer and maintained a larger space on mandatory lane change (the communication delay for lane merging assistance was unnoticeable when it was less than 1.5 s).…”
Section: Cavs and Managed Lanes Managed Lanes Have Been Inmentioning
confidence: 99%
“…e primary reason for using a simply synthetic network is to limit variables for the simulation. Note that the driving behavior parameters for the Wiedemann carfollowing model (for HVs) are the same as those in previous studies [31,41,64,65], representing a subset of the calibrated driving behavior in the I-66 segment in northern Virginia. e demand originated on the mainline is deliberately set higher than usual to create a congested network.…”
Section: Transportationmentioning
confidence: 99%
“…Numerous research studies deal with cluster analysis in traffic. The study presented in [4] shows an analysis of data originating from vehicle trajectories obtained by simulation. Two strategies were implemented: -Two platoon clustering strategies for CACC; an ad hoc coordination strategy and a local coordination strategy‖.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, location-based services, such as path planning [1] and customized Points of Interest (POIs) recommendations [2], have produced a large amount of trajectory data. In turn, trajectory data offer a wealth of information and knowledge that can be applied to many sectors, such as location services [3,4], traffic management [5,6], urban planning [7,8], and animal welfare [9,10]. It is important to accurately discover the semantic information behind the original trajectory data and to interpret the human movement actions described by the trajectory from a semantic perspective.…”
Section: Introductionmentioning
confidence: 99%